TATA LETAK GUDANG AIR MINUM KEMASAN PT. Z DALAM USULAN PERBAIKAN MENGGUNAKAN METODE DEDICATED STORAGE - Putri Endah Suwarni; Lilik Faradiawan; Susanti Sundari; Burhan Nudin; Andrie Oktivendra (Industrika : Jurnal Ilmiah Teknik Industri, 2022)
PT. Z is a company that produces drinking water in 240 ml cups, 330 ml bottles, 600 ml bottles, 1500 ml bottles, and 19 liter gallons. The warehouse owned serves to store the products produced before being distributed to customers.The problems faced by PT. Z is a long product pick-up time because the product placement is done randomly without any display of the product type name in the warehouse and the irregular distance of product placement that has high demand to the warehouse exit and there is no line in every area of the goods storage road which makes it difficult for operators to mobilize. The purpose of this research is to redesign the warehouse to be more efficient so that it can reduce the time and distance of product transfer with the Dedicated Storage method, and provide suggestions for improving the warehouse layout while maintaining the existing warehouse area so that activities run effectively and efficiently and the use of the space requirement becomes more optimal. The results of this study can minimize the displacement distance at the Input/Output (I/O) point where before repairing the product search time for 1 month it takes 235,837 seconds (65.5 hours/month) however, with the proposed product warehouse layout, it is now 175,120 seconds (48 hours/month).